Pengembangan Media Animasi dalam Model Pembelajaran STAD Materi Sistem Peredaran Darah Manusia di SMP - Cahyaningrum, Nadila Eka Okta; Abidin, Zainul; Wedi, Agus (JKTP: Jurnal Kajian Teknologi Pendidikan, 2022)
The development of animation media in the learning model STAD aims to create effective and attractive learning activities so as to improve student learning outcomes. The animation media was developed in learning the human circulatory system in junior high schools. The research method used the Sadiman development model. Product validation is carried out by material experts and media experts. Meanwhile, the target of the field evaluation was class VIII students of SMP Negeri 1 Kauman Ponorogo. Based on the results of the field evaluation, it can be concluded that the animation media in the learning model STAD, the human circulatory system material, is categorized as suitable for use in learning activities. Furthermore, based on the results of the pre-test and post-test that were tested using the Paired Sample T-Test, it was found that there was a difference between the pre-test and post-test results. So it can be concluded that the use of animation media in the learning model STAD for the human circulatory system material in SMP can be applied as a guide in learning activities by teachers to create effective and interesting learning so that it can improve learning student’s outcomes.AbstrakPengembangan media animasi dalam model pembelajaran STAD bertujuan untuk menciptakan kegiatan pembelajaran yang efektif dan menarik sehingga dapat meningkatkan hasil belajar siswa. Media animasi tersebut dikembangkan dalam pembelajaran sistem peredaran darah manusia di SMP. Metode penelitian tersebut menggunakan model pengembangan Sadiman. Validasi produk dilaksanakan oleh ahli materi dan ahli media. Sedangkan sasaran evaluasi lapangan yaitu siswa kelas VIII SMP Negeri 1 Kauman Ponorogo. Berdasarkan dari hasil evaluasi lapangan maka dapat disimpulkan bahwa media animasi dalam model pembelajaran STAD materi sistem peredaran darah manusia tersebut masuk kategori layak digunakan dalam kegiatan pembelajaran. Lebih lanjut, berdasarkan hasil pre-test dan post-test yang diuji menggunakan Uji Paired Sample T-Test diperoleh hasil bahwa terdapat perbedaan antara hasil pre-test dan post-test. Sehingga dapat disimpulkan bahwa penggunaan media animasi dalam model pembelajaran STAD untuk materi sistem peredaran darah manusia di SMP tersebut dapat diterapkan sebagai pedoman dalam kegiatan pembelajaran oleh guru untuk menciptakan pembelajaran yang efektif dan menarik sehingga dapat meningkatkan hasil belajar siswa.